2018
DOI: 10.11114/jets.v6i3.2919
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between the Achievement Goals and Teacher Engagement of Turkish Teachers

Abstract: The aim of this study is to determine the level of achievement goals and teacher engagement of Turkish teachers and the relationship between them if any. Accordingly, the study was conducted with Turkish teachers working in an eastern city and its districts and villages in the school year of 2017-2018. The data were collected using "3x2 Achievement Goal Questionnaire for Teachers" adapted into Turkish by Yerdelen and Padır (2017) and "Engaged Teachers Scale" developed by Yerdelen, Klassen and Durksen (2017). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…At this point, most of the participants believed in the power of the will and reported some positive opinions on the sense of responsibility and competence. Some other researches in the literature indicate that the achievement goals of in-teachers and pre-service teachers increase the level of integration with that job by taking the responsibility of a job (Ürün Karahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, most of the participants believed in the power of the will and reported some positive opinions on the sense of responsibility and competence. Some other researches in the literature indicate that the achievement goals of in-teachers and pre-service teachers increase the level of integration with that job by taking the responsibility of a job (Ürün Karahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ancak görüş yoğunluğu dikkate alındığında sorumluluk bilinci, yeterlik, potansiyel ve emek kavramları öğrenmeyaklaşma yöneliminin baskın olduğunu göstermektedir. Yapılan araştırmalar da öğretmen ve öğretmen adaylarının sahip oldukları başarı yönelimlerinin bir işin sorumluluğunu alarak o işle bütünleşme düzeyini artırdığını göstermektedir (Ürün Karahan, 2018).…”
Section: Sonuç Ve Tartışmaunclassified
“…Put another way, they were less likely to burn out when faced with challenges at work. Karahan (2018) found that, when teachers achieved their goals, they were more likely to maintain engagement and be fulfilled at work. Educator engagement leads to more successful pedagogical outcomes and goal achievement and higher levels of personal career satisfaction and work wellness (Anikin, Lapteva, Kormin, Bondarovskaya, & Poletaeva, 2017).…”
Section: Centring Human Connections In the Education Of Health Professionalsmentioning
confidence: 97%
“…Educators are the keystone of the educational process and have a direct impact on learners and their learning experiences (Alpaslan, Bozgeyikli, & Avci, 2017). Most fully engaged educators love their job, work willingly, establish healthy relationships with their learners, and conduct the educational process successfully (Karahan, 2018). When educators achieve these outcomes and are satisfied with their careers and work performance, learners benefit in several ways.…”
Section: Centring Human Connections In the Education Of Health Professionalsmentioning
confidence: 99%
“…The construct and criterion-related validities of the 3 × 2 achievement goal measurement were preliminary demonstrated on a university education level [ 16 ]. After that, supportive evidence related to the construct and criterion-related validity toward 3 × 2 achievement goal theory was sequentially proposed based on school-aged students across countries and subject domains (e.g., engineering and physical education) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%